Overwhelmed by beauty and faith: review on artistic and religious travelers’ syndromes - Cisneros-Ceh, Damaris; Esquivel-Heredia, Darina; Medina-Vargas, Allan; Azcorra-Perez, Hugo; Chi-Mendez, Claudia Guadalupe; Marin-Cardenas, Alina D.; Mendez-Dominguez, Nina (Frontiers in Behavioral Neuroscience, 2024)
Traveling with the intention of encountering art or seeking purification of the spirit involves retribution of intangible nature and therefore can be expected to be a positive experience; nevertheless, among susceptible travelers, there is also a possibility of experiencing pathological conditions. Although it is colloquially known that beauty lies in the eyes of the beholder, it is necessary to mention that the appreciation of beauty, immensity, or mysticism contained in masterpieces is not perceived only through the eyes but through other sense organs as well. Additionally, this is understood within a cultural framework and through previous knowledge. The reaction triggers a series of somatosensory responses of diverse nature, with a wide range of responses that together constitute a pathological phenomenon that can be defined as syndromic by eliciting signs and symptoms of a physical, physiological, and psychotic nature. Both Stendhal and Jerusalem syndromes are travelers’ syndromes that may occur in response to objectively aesthetic elements saturated with meaning linked to the cultural heritage of contemporary humanity. While Stendhal syndrome evokes physical and psychoemotional symptoms from the contemplation of art, Jerusalem syndrome goes beyond perception, adding delusions of being a religious or prophetic protagonist pursuing individual or collective salvation.